Impact of wind on in-situ burning behavior of spilled oil on open water. (May 2020) - Kong, Depeng; Yang, Hanbing; He, Xu
Abstract: Spilled oil may cause serious environmental pollution and ecological destruction. Thus, an efficient oil spill response is essential to reduce and minimize the impacts seen from an oil spill. In-situ burning (ISB) has been proven to be one of the most convenient and efficient treatment methods for oil spills on sea. When in-situ burning operation is carried out on sea, the wind is usually available. Spilled oil pool fire flame will be blown to tilt with an angle from the vertical direction and the flame length will be stretched. This effect of flame on downstream will be significantly enhanced. It may even cause the burning of spilled oil out of control or hazard the operators near site. Therefore, it is meaningful to study the burning behavior of oil pool fire on open water under wind. A small-scale oil pool fire on open water experiment system was designed, which could simulate the boundary conditions of sea surface ISB. A series of experiments were carried out to study the effects of oil pool diameter, oil layer thickness and wind speed on fire flame length and flame tilt angle. Flame characteristics and temperature of burning system were recorded. This study observes burning behavior to evolve from short pool fire to long declining phase which transient through boilover stage. Dimensionless flame length in pool fire stage increases with wind speed. As expected the flame tilt is strongly influenced by wind speed, tilt angle increase with wind speed. The observed experimental behavior is captured as improvement in the flame length and flame tilt angle models. This study helped better understanding fire behavior in evolving environmental conditions, and the most importantly developed model would help guide better assessment of fire mitigation strategies. Graphical abstract: Image 1 Highlights: Differences in heat transfer process between ISB and limited vessel fires. An improved empirical formula of flame length under wind condition is developed. A flame lilt model is proposed based on the inertial and buoyancy force of flame.